Development Of Metrology And The Role And Importance Of Metrological Supply In Enterprises - Badalov Nomoz Juraboyevich; Shokirov Muxammad Abduraxmonovich; Badalov O’tkirbek Nomoz O’g’li (Genius Journals, 2022)
The main purpose of metrological support in production is to increase the quality of the product at all stages of its creation and use and its competitiveness in the conditions of market relations. The level of metrological supply in production has a direct impact on product quality indicators, with a special focus on metrological supply issues in order to increase the effectiveness of this impact.
Keywords: Metrology; standard; product; aggregate